2018
DOI: 10.1016/j.ekir.2017.12.001
|View full text |Cite
|
Sign up to set email alerts
|

Benefit of Apabetalone on Plasma Proteins in Renal Disease

Abstract: IntroductionApabetalone, a small molecule inhibitor, targets epigenetic readers termed BET proteins that contribute to gene dysregulation in human disorders. Apabetalone has in vitro and in vivo anti-inflammatory and antiatherosclerotic properties. In phase 2 clinical trials, this drug reduced the incidence of major adverse cardiac events in patients with cardiovascular disease. Chronic kidney disease is associated with a progressive loss of renal function and a high risk of cardiovascular disease. We studied … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
41
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
3

Relationship

5
3

Authors

Journals

citations
Cited by 33 publications
(43 citation statements)
references
References 71 publications
(116 reference statements)
1
41
1
Order By: Relevance
“…While clinical trials demonstrate apabetalone beneficially affects inflammation [15], plasma lipid profile [11], and may improve kidney function [13], data in this mechanistic study shows apabetalone also (Fig. 3A-B).…”
Section: Discussionmentioning
confidence: 67%
See 2 more Smart Citations
“…While clinical trials demonstrate apabetalone beneficially affects inflammation [15], plasma lipid profile [11], and may improve kidney function [13], data in this mechanistic study shows apabetalone also (Fig. 3A-B).…”
Section: Discussionmentioning
confidence: 67%
“…Apabetalone also reduced circulating alkaline phosphatase (ALP), a robust and independent predictor of all-cause mortality that contributes to VC progression [13,14]. Notably, a single dose provided to CKD patients rapidly resulted in reduction of several inflammatory cytokines, including IL-6 [15]. Canonical pathway analysis of plasma proteomics predicted downregulation of IL-6 and bone morphogenetic protein signaling pathways, which both promote VC [15].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Apabetalone is the first BET inhibitor to be evaluated in human clinical trials for treatment of chronic disease, and has been shown to target multiple processes that underlie CVD, including reverse cholesterol transport, atherogenesis, thrombosis and vascular inflammation [9, 10]. A recent pharmacokinetic study of apabetalone treatment in patients with late stage CKD revealed that a single dose of apabetalone rapidly downregulated multiple CKD and CVD protein markers, and associated molecular pathways [11]. Moreover, in the phase II clinical studies with apabetalone, patients treated with apabetalone were less likely to experience a major adverse cardiovascular event (MACE) and experienced reductions in CKD risk factors such as ALP [9].…”
Section: Introductionmentioning
confidence: 99%
“…Apabetalone (RVX-208) is a small molecule inhibitor of BET proteins (BETi) that selectively targets the second BD (BD2) of BET proteins, reducing their transcriptional activity [9,10]. Preclinical and clinical studies have shown that apabetalone modulates the expression of proinflammatory and proatherosclerotic genes in models of atherosclerosis and in patients with coronary artery or chronic kidney disease [11][12][13][14][15][16][17]. Apabetalone also impacts the transcription of APR genes in primary human hepatocytes (PHH), including C-reactive protein (CRP) [12,13,16].…”
Section: Introductionmentioning
confidence: 99%